Augmentation effect of postprandial hyperinsulinaemia on growth of human hepatocellular carcinoma. Issue 1 (1st July 2002) - Saito, K; Inoue, S; Saito, T; Kiso, S; Ito, N; Tamura, S; Watanabe, H; Takeda, H; Misawa, H; Togashi, H; Matsuzawa, Y; Kawata, S
Abstract : Background: Cirrhotic patients with hepatocellular carcinoma (HCC) frequently have impaired glucose metabolism. Aims: To investigate whether impaired glucose metabolism affects the growth rate of the tumour. Patients and methods: Tumour doubling time (DT), assessed by ultrasound imaging analysis, was measured in 60 patients with single small HCC (diameter <30 mm). DT was compared with plasma insulin and glucose concentrations following the oral glucose tolerance test (OGTT). The effect of continuous infusion of octreotide (a somatostatin analogue 200 μg/day) for three months on DT in five cases was assessed. Results: The 60 patients were divided into two groups because the median DT was 140 days: rapid growth group (DT ≤140 days, n=30) and slow growth group (DT >140 days, n=30). Fasting plasma insulin concentration and area under the plasma insulin curve (AUCins ) of the OGTT (10.4 (6.2) μU/ml and 262 (152) μU/ml/h, respectively; mean (SD)) in the rapid growth group were significantly higher than those in the slow growth group (7.6 (4.3) and 146 (140), respectively) (p=0.041 and p=0.0006, respectively). In contrast, fasting plasma glucose concentration and area under the plasma glucose curve (AUCgluc ) in the rapid growth group were significantly lower than those in the slow growth group (p=0.0003 and p=0.0012, respectively). Univariate and multivariate analyses of logistic regression models demonstrated that AUCins was a significant factor contributing to the growth rate of HCC (p=0.001 and p=0.016, respectively). AUCins significantly decreased after octreotide treatment (p<0.02) but AUCgluc did not significantly change. DT after treatment increased in three of the five patients and could not be calculated in the remaining two patients because of no change in the diameter of the tumour. Conclusions: These data suggest that postprandial hyperinsulinaemia is associated with accelerated HCC growth.